Protecting Migrant Workers' Rights in Overseas Work Accidents under Article 17(1) Permenaker No. 18/2018 - Ardhiyanti, Fitri; Khayatudin, Khayatudin; Mardian Yoel, Siciliya (Universitas Negeri Gorontalo, 2025)
This study examines the regulations governing work accident insurance claims issued by BPJS Employment, which serves as a stakeholder for Indonesian Migrant Workers (PMI) in their host countries. Often, PMIs encounter difficulties in claiming the Work Accident Insurance (JKK). The purpose of this research is to elucidate the procedures for filing work accident claims for PMIs. This study adopts a normative juridical method. The findings indicate that there are two stages involved in claiming JKK for PMIs in the host country. The first stage must be carried out within a maximum of seven days after the work accident occurs, accompanied by the required supporting documents. The second stage must be completed within a maximum of seven days after the worker has fully recovered. Furthermore, PMIs who are already in the host country but cannot claim their work accident benefits particularly those requiring treatment in Indonesia are entitled to compensation as stipulated in Article 17 paragraphs (2) and (4) of Minister of Manpower Regulation Number 18 of 2018